2000
DOI: 10.1016/s0014-5793(00)01615-x
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and characterization of a root specific high‐affinity sulfate transporter from Arabidopsis thaliana

Abstract: Hst1At (accession number AB018695) was identified from the Arabidopsis thaliana sequencing project on BAC T3F12, and the corresponding cDNA was isolated by reverse transcription-PCR. Southern blot analysis reveals a single copy of this gene. The cDNA encodes a root specific sulfate transporter of 649 amino acids. Heterologous expression of hst1At in a sulfate transport deficient yeast mutant shows that this gene encodes a high-affinity transport system (V V2 W WM). The transcript relative abundance increases i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
94
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(98 citation statements)
references
References 23 publications
3
94
0
1
Order By: Relevance
“…Kinetic analysis of the sulfate uptake isotherm obtained in a range of low sulfate external concentrations (1-50 mM; Fig. 2), revealed that ZmST1;1 has a high affinity for sulfate, with an apparent K m value (14.6 6 0.4 mM) similar to those of other plant high-affinity sulfate transporters (Smith et al, 1995;Smith et al, 1997;Takahashi et al, 2000;Vidmar et al, 2000;Yoshimoto et al, 2002;Howarth et al, 2003). Taken as a whole, our findings suggest a role of ZmST1;1 in mediating the root highaffinity sulfate uptake from the soil solution.…”
Section: Discussionmentioning
confidence: 73%
“…Kinetic analysis of the sulfate uptake isotherm obtained in a range of low sulfate external concentrations (1-50 mM; Fig. 2), revealed that ZmST1;1 has a high affinity for sulfate, with an apparent K m value (14.6 6 0.4 mM) similar to those of other plant high-affinity sulfate transporters (Smith et al, 1995;Smith et al, 1997;Takahashi et al, 2000;Vidmar et al, 2000;Yoshimoto et al, 2002;Howarth et al, 2003). Taken as a whole, our findings suggest a role of ZmST1;1 in mediating the root highaffinity sulfate uptake from the soil solution.…”
Section: Discussionmentioning
confidence: 73%
“…Judging from the close sequence similarities with other functional sulfate transporters in plants (Smith et al, 1995(Smith et al, , 1997Takahashi et al, 1997Takahashi et al, , 2000Vidmar et al, 1999Vidmar et al, , 2000Shibagaki et al, 2002;Yoshimoto et al, 2002Yoshimoto et al, , 2003Howarth et al, 2003), it is suggested that SULTR4;1 and SULTR4;2 belong to the proton/ sulfate cotransporter family and may use DpH across the tonoplast as a motive force for the efflux of sulfate. Database searches found several other SULTR4 transporters in various plant species.…”
Section: Discussionmentioning
confidence: 99%
“…HVST1 from barley (Hordeum vulgare) showed similar characteristics (Smith et al, 1997;Vidmar et al, 1999). More recently, Arabidopsis thaliana SULTR1;1 and SULTR1;2 (Takahashi et al, 2000;Vidmar et al, 2000;Shibagaki et al, 2002;Yoshimoto et al, 2002) were established to have functional properties similar to SHST1 and HVST1. Arabidopsis SULTR1;1 and SULTR1;2 were localized in the root hairs, epidermis, and cortex cells, and the respective abundances of mRNAs for these transporters increased upon sulfur starvation.…”
Section: Introductionmentioning
confidence: 99%
“…In Arabidopsis, two high-affinity sulfate transporters, SULTR1;1 and SULTR1;2, facilitate the initial uptake of sulfate into the roots (Takahashi et al 2000;Vidmar et al 2000;Shibagaki et al 2002; Yoshimoto et al 2002). These transporters are expressed in the epidermis and cortex of roots, and their transcripts can accumulate through sulfur depletion to maximize sulfate uptake for efficiently using limited amounts of sulfur in the soil environment (Takahashi et al 2000;Vidmar et al 2000;Shibagaki et al 2002; Yoshimoto et al 2002).…”
Section: ϫmentioning
confidence: 99%
“…Accordingly, excess amounts of selenate and chromate taken up from the environment can affect the cellular function of living organisms and sometimes have lethal effects. Indeed, several mutants lacking sulfate transporter genes have been isolated from yeast and plants by using the toxic effects of selenate and chromate as sulfate analogs (Smith et al 1995a, b;Cherest et al 1997;Shibagaki et al 2002).In Arabidopsis, two high-affinity sulfate transporters, SULTR1;1 and SULTR1;2, facilitate the initial uptake of sulfate into the roots (Takahashi et al 2000;Vidmar et al 2000;Shibagaki et al 2002; Yoshimoto et al 2002). These transporters are expressed in the epidermis and cortex of roots, and their transcripts can accumulate through sulfur depletion to maximize sulfate uptake for efficiently using limited amounts of sulfur in the soil environment (Takahashi et al 2000;Vidmar et al 2000;Shibagaki et al 2002; Yoshimoto et al 2002).…”
mentioning
confidence: 99%